A strange cause of nasal blockage and anemia in an infant - Thakur, Rashika; Sharma, Yash Pal; Sharma, Shruti (International Journal of Contemporary Pediatrics, 2024)
Leeches are sanguivorous parasites causing infestation in humans and other warm-blooded mammals, mainly affecting older children and adults with most common site of attachment being nasopharynx. We present a case of severe anaemia and growth failure in an eight-month-old infant due to nasopharyngeal leech infestation with symptoms of nasal blockade and blood-tinged nasal exudation. The child showed significant improvement on follow-up after removal of the leech.